The influence of school principals' academic supervision on the quality of learning through teacher professionalism as an intervening variable - Ikrima Mailani (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
The present study reviews the impact of the principal academic supervision on the teacher professionalism and learning quality in SDIT. It tests the contribution of teacher professionalism as a mediating variable. This study is quantitative research using a survey method. A questionnaire gathered the data and was analysed using path analysis based on Structural Equation Modelling with Partial Least Squares (SEM-PLS). The result is that the principal’s academic supervision positively affects teacher professionalism, and teacher professionalism positively and significantly influences learning quality. Nevertheless, the principal’s academic supervision does not considerably influence the learning quality. The other important finding is that teacher professionalism fully mediates the relationship between the principal academic supervision and learning quality. It can be said that the quality of learning can be improved by constantly developing the professionalism of teachers, which is fostered through good academic supervision by the principal.